Comparison of Prolene Sutures Versus Skin Staples for Mesh Fixation in Lichtenstein Inguinal Hernioplasty: A Randomized Controlled Trial: Prolene Sutures Versus Skin Staples for Mesh Fixation in Lichtenstein Inguinal Hernioplasty - Ahmad, Adeel; Janjua, Muhammad Haris; Mahmood, Sharjeel; Siddiqui, Aasiya; Elahi, Faizan; Sarwar, Muhammad Zeeshan; Naseem, Muhammad Yasir (Pakistan Journal of Health Sciences, 2026)
Chronic postoperative groin pain following Lichtenstein inguinal hernia repair is commonly attributed to nerve irritation during mesh fixation. Alternative fixation methods, such as skin staples, have been proposed to reduce postoperative pain. Objectives: To compare postoperative pain outcomes following mesh fixation with Prolene sutures versus skin staples in Lichtenstein inguinal hernioplasty. Methods: This randomized controlled trial was conducted at Mayo Hospital, Lahore. 132 adult male patients undergoing elective unilateral Lichtenstein inguinal hernioplasty were randomized to mesh fixation using either Prolene sutures or stainless-steel skin staples. Postoperative pain was assessed using the Visual Analogue Scale (VAS) on postoperative days 1, 14, 30, and 90. Statistical analysis included the Mann–Whitney U test, chi-square test, and logistic regression. Results: Baseline characteristics were comparable between groups. Median VAS on day 1 was higher in the Prolene group compared to the staple group, but pain scores declined significantly in both groups over time. By day 90, 37.9% of patients were pain-free, with no significant difference in pain-free rates between fixation methods (p=0.858). No independent predictors of persistent pain were identified. Conclusions: Mesh fixation with Prolene sutures and skin staples results in comparable postoperative pain outcomes. Fixation choice may therefore be guided by surgeon preference and operative considerations.